CORPORATE CONFLICT: PROBLEM OF MODERN UDERSTANDING (World Bulletin of Management and Law, 2023)
In the article considers the various approaches to the concept of "corporate conflict". Particular attention is focused on the issue of the correlation of corporate conflict with related concepts. It is noted that a characteristic feature of corporate conflicts is becoming increasingly visible their multilevel feature, the presence of conflicts of interest within each group of different participants in corporate relations. In this regard, there is a wide range of diverse classification features of corporate conflict. With this in mind, modern economic realities aim at the necessity not only to streamline, but also to bring together the above economic-normative concepts, at the same time differentiating and clearly structuring them. The necessity for attention to these issues stems, in particular, from the growing popularity of mergers and acquisitions of various companies.